Preparation and Characterization of the Complex Attuplgite-polyazo m-phenelen p-kresole as a Composite nano Material - Ibrahim, Alla Abdulkareem; Himdan, Takialdin Abdulhadi; MohammedAbuzaid, Yousif Ibrahim (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this study a new composite nano material was prepared and characterized through the polymerization of inter attuplgie layered m-phenylendiamine with p-kresol. The results indicated that the propagated polymer separated the clay aluminosilicate layers as a two dimensional nano-sheets soaked in the prepared polymer matrix with losing the original fibrous structure of Attuplgite clay.